Phylogenomics and generic limits of Dypsidinae (Arecaceae), the largest palm radiation in Madagascar. Issue 6 (24th August 2022) - Eiserhardt, Wolf L.; Bellot, Sidonie; Cowan, Robyn S.; Dransfield, John; Hansen, Lars Emil S.F.; Heyduk, Karolina; Rabarijaona, Romer N.; Rakotoarinivo, Mijoro; Baker, William J.
Abstract: With 178 species, palm subtribe Dypsidinae is one of the largest plant radiations on Madagascar. A well‐resolved species‐level phylogeny is required not only to unpick the drivers of this spectacular radiation, but also to define natural and useful generic limits in this taxonomically difficult group. The only recent taxonomic revision of Dypsidinae recognised just four genera, including the large genus Dypsis (currently with 172 species), which was considered impossible to divide further based on morphology alone. Here we describe the first comprehensively sampled species‐level phylogeny of Dypsidinae, including 157 described species (88% of the subtribe) as well as 10 samples of uncertain taxonomic identity (potentially new to science). Our tree is based on target sequence capture data for 161 nuclear DNA loci. The phylogenetic relationships recovered render Dypsis s.l. paraphyletic, requiring the resurrection of two previously synonymised genera. In total, we recognise six genera in Dypsidinae ( Dypsis, Chrysalidocarpus, Marojejya, Vonitra, Lemurophoenix, Masoala ), all of which are monophyletic and consistent with morphology.